Immunisation of chickens with inactivated and/or infectious H9N2 avian influenza virus leads to differential immune B-cell repertoire development - Dascalu, Stefan; Sealy, Joshua E.; Sadeyen, Jean-Remy; Flammer, Patrik G.; Fiddaman, Steven; Preston, Stephen G.; Dixon, Robert J.; Bonsall, Michael B.; Smith, Adrian L.; Iqbal, Munir (Frontiers in Immunology, 2024)
Avian influenza viruses (AIVs) are a major economic burden to the poultry industry, and pose serious zoonotic risk, with human infections being reported every year. To date, the vaccination of birds remains the most important method for the prevention and control of AIV outbreaks. Most national vaccination strategies against AIV infection use whole-virus inactivated vaccines, which predominantly trigger a systemic antibody-mediated immune response. There are currently no studies that have examined the antibody repertoire of birds that were infected with and/or vaccinated against AIV. To this end, we evaluate the changes in the H9N2-specific IgM and IgY repertoires in chickens subjected to vaccination(s) and/or infectious challenge. We show that a large proportion of the IgM and IgY clones were shared across multiple individuals, and these public clonal responses are dependent on both the immunisation status of the birds and the specific tissue that was examined. Furthermore, analysis reveals specific clonal expansions which are restricted to particular H9N2 immunisation regimes. These results indicate that both the nature and number of immunisations are important drivers of the antibody responses and repertoire profiles in chickens following H9N2 antigenic stimulation. We discuss how the repertoire biology of avian B cell responses may affect the success of AIV vaccination in chickens, in particular the implications of public versus private clonal selection.